Electrochemical and Tribocorrosion Study of D2 Steel Coated with TiN with C or Cr Addition Films in 3.5 wt% of NaCl in Bi-Distillated Water Solution - García-Bustos, Ernesto David; Maxemin-Lugo, Diego; Diez-Torres, Norberto; López-Perrusquia, Noé; Doñu-Ruiz, Marco Antonio; Flores-Martinez, Martin; Restrepo, Johans; Muhl-Saunders, Stephen (Materials, 2025)
Food security is one of the main problems in several countries. In food processing the cutting operation is very important as the operation is basic to food preparation. Due to cutting tools being exposed to a high-demand environment that includes high contact pressure, a corrosive atmosphere, and a high-speed process, they are subject to high mechanical and corrosive wear that reduces their lifetime and efficiency. Tribocorrosion is one of the main phenomena that reduces the lifetime and efficiency of cutting tools. This work presents electrochemical and tribocorrosion studies of D2 steel surfaces coated with TiN, TiCN, and TiCrN films. The samples were coated by a commercial source, using the PVD-cathodic arc technique. The crystalline structure of TiN and TiCN films presented a TiN and Ti phase, while the crystalline structure of TiCrN showed CrN and Cr phases. The films exhibited good adhesion, but the surfaces coated with TiN and TiCN films presented lower hardness. Although the TiN, TiCN, and TiCrN films showed better wear and corrosion resistance than the D2 steel surfaces, the inclusion of C and Cr in the TiN films decreased the TiN wear and electrochemical resistance in 3.5% (w/w) of NaCl solution.